Vertical variation and source evaluation of VOCs and inorganic pollutants in a university building. Issue 4 (2nd October 2018) - Yurdakul, Sema; Civan, Mihriban; Doğan, Güray; Üzmez, Özlem Özden; Gaga, Eftade O.; Döğeroğlu, Tuncay; Ayaklı, Gül; Tuncel, Gürdal
Abstract: Concentrations of volatile organic compounds (VOCs) and inorganic pollutants including sulfur dioxide (SO2 ), nitrogen dioxide (NO2 ), and ozone (O3 ) were measured using passive samplers in both indoor and outdoor environments at 2, 5, 8, 13, 17, 24, and 29 m from the ground level at a high-rise building in the Middle East Technical University campus in Ankara, Turkey. The measured indoor concentrations of ∑24 VOCs were highly variable, ranging from 98 μg m −3 (at the ground floor) to 235.3 μg m −3 (at the fourth floor), while the outdoor concentrations varied between 96.8 μg m −3 (at the seventh floor) and 189.8 μg m −3 (at the ground level). Outdoor concentrations of inorganic pollutants ranged between 58 μg m −3 at the ground floor and 26 μg m −3 at the ninth floor for SO2, and 59.9 μg m −3 at the ground floor and 31.2 μg m −3 at the ninth floor for NO2 . A similar decreasing trend with altitude was also observed for indoor concentrations of these pollutants. Indoor and outdoor O3 concentrations did not change with altitude. Statistically significant correlations were found between indoor and outdoor concentrations of some of the measured NO2, SO2 toluene, octane, nonane and 1, 2-dichlorobenzene, indicating moderate-to-strong relationships between their indoor and outdoor concentrations. The factor analysis revealed six factors for both indoor and outdoor data. Traffic was found to be the highest contributor to the measured VOCs, SO2, and NO2 concentrations, which was followed by painting activities.